2021
DOI: 10.1002/jsfa.11122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proanthocyanidins on the pasting, rheological and retrogradation properties of potato starch

Abstract: BACKGROUND Proanthocyanidins (PAS) were complexed with potato starch (PS) to prepare polyphenol–starch complexes. The pasting, rheological and retrogradation properties of the complexes were investigated. RESULTS The addition of PAS markedly affected the pasting, rheological and retrogradation properties of PS, especially at a concentration of 5% (w/w). Rapid viscosity analysis indicated that PAS significantly changed the viscosity, breakdown and setback value of PS. The rheological results showed that PAS dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…This finding was in agreement with the BD result of RVA. The same trends of K value and hysteresis ring area of starch added with polysaccharides have been reported before, and these results indicated that the relative stability and uniformity of the starch gel structure was enhanced [ 4 , 19 ].…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…This finding was in agreement with the BD result of RVA. The same trends of K value and hysteresis ring area of starch added with polysaccharides have been reported before, and these results indicated that the relative stability and uniformity of the starch gel structure was enhanced [ 4 , 19 ].…”
Section: Resultssupporting
confidence: 78%
“…This finding was in agreement with the BD result of RVA. The same trends of K value and hysteresis ring area of starch added with polysaccharides have been reported before, and these results indicated that the relative stability and uniformity of the starch gel structure was enhanced [4,19]. The value of n is inversely correlated with the pseudoplasticity degree of the entire system [31], PPC replacement decreasing the n value, for PPC1 the most.…”
Section: Steady Shear Analysissupporting
confidence: 81%
See 3 more Smart Citations